1998
DOI: 10.1074/jbc.273.36.22904
|View full text |Cite
|
Sign up to set email alerts
|

Heparinase II from Flavobacterium heparinum

Abstract: Heparinase II (no EC number) is one of three lyases isolated from Flavobacterium heparinum that degrade heparin-like complex polysaccharides. Heparinase II is unique among the heparinases in that it has broad substrate requirements and possesses the ability to degrade both heparin and heparan sulfate-like regions of glycosaminoglycans. This study set out to investigate the role of cysteines in heparinase II activity. Through a series of chemical modification experiments, it was found that one of the three cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The strong preference of heparinase II for the unsulfated glucuronate-containing linkage of O2 is consistent with the observation that heparinase II might contain two active sites, one of which is heparinase I-like, cleaving primarily heparinlike linkages, whereas the other site is heparinase III-like and cleaves primarily heparan sulfate-like linkages (17). In accordance with this hypothesis, we have identified a particular cysteine residue, cysteine 348, which is critical for the breakdown of heparin but not heparan sulfate by heparinase II (17).…”
Section: Does Heparinase II Act Exolytically or Endolytically?supporting
confidence: 60%
See 1 more Smart Citation
“…The strong preference of heparinase II for the unsulfated glucuronate-containing linkage of O2 is consistent with the observation that heparinase II might contain two active sites, one of which is heparinase I-like, cleaving primarily heparinlike linkages, whereas the other site is heparinase III-like and cleaves primarily heparan sulfate-like linkages (17). In accordance with this hypothesis, we have identified a particular cysteine residue, cysteine 348, which is critical for the breakdown of heparin but not heparan sulfate by heparinase II (17).…”
Section: Does Heparinase II Act Exolytically or Endolytically?supporting
confidence: 60%
“…In addition, recombinant heparinase II and the heparinase mutant protein, C348A, where cysteine-348 is changed to alanine were expressed in Escherichia coli (17). Protein expression, isolation, and purification was carried out as described (17).…”
Section: Methodsmentioning
confidence: 99%
“…The results from these mapping studies indicated that of the three cysteines, present in HepII, Cys-348 was uniquely susceptible to chemical modification by sulfhydryl-reactive reagents. Mutation of this cysteine (C348A) resulted in a selective loss of activity toward heparin but not toward heparan-sulfate (24). Indeed, the HepII structure indicates that Cys-348 is the only cysteine with a surface-accessible sulfhydryl group.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis and Chemical Modification Studies-Previous structure-function studies of P. heparinus HepII have been carried out through the complementary use of chemical modification and site-directed mutagenesis (21,24,25). In particular, these studies focused on the potential catalytic role of cysteine and histidine residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation